Return to Sport Testing After Arthroscopic Shoulder Surgery in Adolescent Patients. Issue 5 (31st May 2022) - Anderson, Kathryn G.; Roman, Dylan; Varakitsomboon, Shing; Weaver, Adam; Saper, Michael G.
Background: Readiness for return to sport (RTS) after surgery can be assessed using strength and functional performance testing. However, data regarding RTS testing after arthroscopic shoulder stabilization in adolescent patients is limited. Purpose: To investigate the results of strength and functional RTS testing following arthroscopic stabilization in adolescent patients with shoulder instability. Methods: A retrospective review of medical records was performed to identify adolescent patients who underwent arthroscopic shoulder stabilization and subsequent RTS testing between April 2017 and April 2020. Surgeries were performed by a single sports medicine fellowship-trained surgeon; RTS assessments were performed at the primary institution's sports rehabilitation clinic by a licensed physical therapist. Patient demographics, operative details, patient-reported outcome measures (PROMs) (VAS, Tegner, ASES, QuickDASH), and RTS testing results were collected. PROMs were obtained at the time of the RTS test. The recovery of muscle strength was defined by a limb symmetry index (LSI) ≥90%. Differences between the involved and uninvolved limbs were analyzed. Correlations between RTS testing results and PROMs were examined. Results: 24 patients (62.5% male) were identified with mean age of 15.5 years (range, 13-21 years). Football was the most common primary sport played (33.3%). 58.3% of patients underwent surgery on their dominant shoulder. 21 patients had isolated anterior repairs, two had combined anterior/posterior repairs, and one had an isolated posterior repair. RTS testing was performed at a mean of 6.02 ± 0.64 months postoperatively. All PROMs improved significantly from pre-operative to the time of RTS testing (p<0.0001). All patients (n=24) failed at least one component of the RTS testing (Table 1). Pre-operative Tegner scores were positively correlated with involved isokinetic external rotation symmetry (r=0.383, p<0.05) and with closed kinetic chain upper extremity stability test (CKCUEST) performance (r=0.577, p<0.005). Post-operative Tegner and ASES scores were positively correlated with involved isometric internal rotation LSI (r=0.418, p<0.05) and CKCUEST performance (r=0.383, p<0.05), respectively. Isometric External Rotation LSI was positively correlated with the Isokinetic External Rotation LSI at 180°/sec for the surgical limb (r=0.57, p<0.01). Conclusion: At 6-months postoperative, shoulder strength and stability deficits persist in the surgical limb of adolescent patients. PROMs improve significantly from pre-operative to time of RTS testing. Tegner and ASES scores may be associated with objective shoulder strength and stability measurements. Table 1. Return-to-Sport Pass Criteria and Percentage of Patients Who Passed